From their eyes: Deaflympic athletes' and coaches' perspectives on mental training - Markov-Glazer, Alon; Elbe, Anne-Marie; Schliermann, Rainer (Frontiers in Sports and Active Living, 2025)
IntroductionSport psychology research has largely overlooked athletes with hearing impairments competing in Deaflympic sports, the designated elite sporting movement for this population. This study therefore explored Deaflympic athletes' and coaches' perspectives on mental training in the elite Deaf sports.MethodsA qualitative approach was used, involving six focus group interviews with 23 athletes (Mage = 33.09; 26.1% female) and four coaches from individual and team Deaf sports. Data were analyzed using reflexive thematic analysis.ResultsThree themes emerged: sport psychology consultation, the influence of visual orientation on psychological skills and demands, and Deaf sport culture and communication. While participants expressed strong interest in sport psychology, engagement with professionals was limited by accessibility issues, lack of sign language-fluent consultants, and structural barriers. Deaf athletes reported adapting some techniques to match their visual-spatial orientation and both advantages and challenges of visual reliance in sports. Distinct communication dynamics between native signers and spoken-language users within Deaf teams were also revealed.DiscussionThese findings highlight the importance of culturally sensitive sport psychology frameworks that support the needs and preferences of Deaflympic athletes and promote equitable access to effective mental training resources.